Candle Flame Synthesis and Electrochemical Behavior of Chain-like Carbon Nano-onions on 304 Stainless Steel - Saifon Kruehong (Science Faculty of Chiang Mai University, 2019)
The feasibility of chain-like carbon nano-onions on 304 stainless steel substrate by candle flame synthesis was described. The carbon nanomaterials were synthesized at 600oC for 180 seconds on the 1 cm × 0.5 cm 304 stainless steel wafers. SEM and TEM analysis results of carbon nanomaterials showed that it was chain-like carbon nano-onions of 40-70 nm in diameter with graphite structure. The ratio of the G and D band intensity (IG/ ID) of Raman analysis was 1.03. In addition, the chain-like carbon nano-onions-coated 304 stainless steel was applied as working electrode in three-electrode system. The electrochemical behavior of chain-like carbon nano-onions was characterized by cathodic polarization in KOH and H3PO4 solutions. Electrocatalytic behavior of chain-like carbon nano-onions on oxygen reduction and hydrogen evolution reaction was presented in comparison with uncoated stainless steel wafer.